Treatment and Renal Outcomes Up to 96 Weeks After Tenofovir Alafenamide Switch From Tenofovir Disoproxil Fumarate in Routine Practice. Issue 2 (22nd May 2021) - Toyoda, Hidenori; Leong, Jennifer; Landis, Charles; Atsukawa, Masanori; Watanabe, Tsunamasa; Huang, Daniel Q.; Liu, Joanne; Quek, Sabrina Xin Zi; Ishikawa, Toru; Arai, Taeang; Yokohama, Keisuke; Chuma, Makoto; et al.
Abstract : Background and Aims: Real‐world data for treatment effectiveness and renal outcomes in chronic hepatitis B (CHB) patients who were switched to the new and safer prodrug tenofovir alafenamide (TAF) from tenofovir disoproxil fumarate (TDF) are limited. Therefore, we aimed to evaluate treatment and renal outcomes of this population. Approach and Results: We analyzed 834 patients with CHB previously treated with TDF for ≥12 months who were switched to TAF in routine practice at 13 US and Asian centers for changes in viral (HBV DNA < 20 IU/mL), biochemical (alanine aminotransferase [ALT] < 35/25 U/L for male/female), and complete (viral+biochemical) responses, as well as estimated glomerular filtration rate (eGFR; milliliters per minute per 1.73 square meters) up to 96 weeks after switch. Viral suppression ( P  < 0.001) and ALT normalization ( P  = 0.003) rates increased significantly after switch, with a trend for increasing complete response ( P trend = 0.004), while the eGFR trend ( P trend  > 0.44) or mean eGFR ( P  > 0.83, adjusted for age, sex, baseline eGFR, and diabetes, hypertension, or cirrhosis by generalized linear modeling) remained stable. However, among those with baseline eGFR < 90 (chronic kidney disease [CKD] stage ≥2), mean eGFR decreased significantly while on TDF ( P  = 0.029) but not after TAF switch ( P  = 0.90). By week 96, 21% (55/267) of patients with CKD stage 2 at switch improved to stage 1 and 35% (30/85) of CKD stage 3‐5 patients improved to stage 2 and 1.2% (1/85) to stage 1. Conclusions: Overall, we observed continued improvement in virologic response, ALT normalization, and no significant changes in eGFR following switch to TAF from TDF. Abstract :